IRAQIBACTER AS A NEW EMERGING PATHOGEN - Farkad Hawas Musa; Zainab Agab Altaee; Hanan Yousif Rasheed (Central Asian Journal of Medical and Natural Science, 2023)
As a result of its rapid development of resistance to routinely used antimicrobials, Iraqibacter (Acinetobacter baumannii) has emerged as a major hospital infection. It has lately come to light as a major reason why troops returning from Iraq and Afghanistan suffer from crippling soft tissue infections. It is widely believed, and supported by the available research, that the increased rates of infection are attributable to the widespread contamination of hospitals worldwide by A. baumannii, which is becoming more resistant to antimicrobials.